Parental Stress of Pakistani Families with Children who Have Developmental Disabilities - Laraib Ramzan, Amna Rashid, Saba Aziz, Sehar Batool, Saba Yaqoob, Muhammad Azzam Khan, Arslan Saleem Chugtai, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The goal of this research was to find out what factors were associated with these parenting effects in Pakistani mothers and dads who had children with intellectual disability (ID) or autism spectrum disorders (ASD) A total of 191 parents agreed to take part in the study, 100 of whom had a child with ADS and 91 of whom had a child with ID. Each participant filled out standardized parenting stress scale rating scales and provided demographic data during the interview. Families who have children with Autism and ID have higher emotional state, according to structural equation modelling. Objective: To find out parental stress of Pakistani families with children who have developmental disabilities. Methodology: The cross-sectional study was conducted through five different organizations in Lahore, Pakistan (Bases, Rising sun, Dimensions, Autism resource center, Oasis) and from two hospitals (Mayo Hospital Lahore and Sheikh Zaid Hospital). Standardized questionnaire (Parental stress scale) was used. Data was collected through standardized questionnaire after taking inform consent and distributed among the parents with children that have special needs (ASD and ID) Parents were asked to complete a questionnaire. Result scores were recorded for every respondent. The data was analyzed by “Statistical Package for Social Sciences” SPSS (version 22.0). Results: Using a standardized questionnaire, it was shown that the emotional well-being of families with children with ASD and ID was much worse, with both mothers and fathers reporting emotional exhaustion. Stress was exacerbated by a lack of emotional well-being. ASD parents show high percentage of 72.2% and ID parents show highest percentage of 61.1% so according to the given standardized questionnaire points the higher the percentage the higher the stress level. While raising a kid with neurological disabilities has a roughly comparable effect on Pakistani families as it does on parents in other countries, there are evidence that children with ASD and ID provide particular challenges to these families. Conclusion: Parents of both children face higher stress level. High level of parent stress needs timely counselling of the parents about the circumstances that they need to be encountered with having an abnormal child. They shall be aware with the techniques to deviate their mind from the most recurring point of stress. Keywords: Autism spectrum disorder, Intellectual disability, Parental stress, Pakistan, Health, developmental disability